Effect of neutron irradiation on electrical properties of bi2sr2 cacu2 (Bi-2212) phase superconductor - Hamid N.A.; Mohiju Z.A.; Abdullah Y. (Trans Tech Publications Ltd, 2023)
Binary alloys; Calcite; Calcium carbonate; Copper oxides; Defects; Flux pinning; Microstructure; Molar ratio; Neutron sources; Phase structure; Radiation; Scanning electron microscopy; Solid state reactions; X ray diffraction; Bi-2212 phase; Enhanced flux pinning; Flux pinning centers; Pinning properties; Sample preparation; Solid state reaction method; Superconducting phase; Superconducting properties; Neutron irradiation